Apie kai kurias šiuolaikines aikščių formavimo tendencijas Lietuvoje - Grunskis, Tomas (Journal of Architecture and Urbanism, 2009)
On some contemporary square formation trends in LithuaniaTwenty years of development in a town’s history is not a long period of time especially provided that the sociocultural context conditions for such a development may be defined as “favorable” or “normal”. Under conditions of accelerated urbanization, however, when a town is undergoing particularly rapid development, which is even more encouraged by conditions of the context, the whole situation looks by far worse. Throughout the 20th century Lithuania underwent two stages of such an accelerated urbanization. During the first stage of such an urbanization, at the time of the first Lithuanian Republic (1918–1940), the concept of a national capital was conceived and rapidly developed. As soon as it was realized within 20 years in Kaunas, a capital city of European level was formed not only with all the attributes characteristic of a town of the type, but also with its content – urban culture. It is a consistent pattern that the results of urban development can be seen most clearly not only in expansion of a town’s territory (outward development), but also through changes in its “inner” or public spaces. Within the aforementioned period, when it was so important to entrench the ideology of the nation state, new monuments representing a national idea occurred in public spaces (squares) of major Lithuanian towns, and even such spaces were reconstructed in a new manner (Fig. 1). Similar urban development – although on a fairly accelerated scale - has been carried out during the recent decade, when starting from 1995 to 2008 the capital city and other major Lithuanian towns were growing and developing extremely extensively. As for the changes in urban public spaces, the situation is far worse. The last significant period of public space formation goes back to the soviet occupation times, and within recent 18 years of independence just a few town squares have been formed or reformed. The present situation might be determined by the fact that the key social power entities, planning for the future of a town and most actively participating in its formation – private capital and self-government (rarely, the state) – have different understanding of urban public space significance to the town itself as well as its community, and also have different capabilities to change them. With commercial logic of benefit, typical under conditions of capital prevalence, an, undeveloped space in a town center can be hardly explainable in commercial terms, especially where land is expensive; and only in rare cases the commercial logic can appreciate real value added and social attraction created by the urban public space. On the one hand, in conditions of urban development under rapid and wild capitalism the self-government lacks leverage and power to implement its duties, form and/or take care of public spaces in a town. On the other hand, it should be taken into consideration that tradition of self-government and public space has been terminated and exterminated in Lithuania for half a century.Article in Lithuanian.Santrauka. Straipsnyje aptariama šiuolaikinė miesto pagrindinių aikščių formavimo situacija Lietuvoje, išskiriant ir apibūdinant kelis svarbiausius bruožus. Čia analizuojama kintanti miesto viešųjų erdvių samprata ir jų pavyzdžiai, kintanti miesto viešųjų erdvių tipologija bei kintantys visuomenės reikalavimai aikšių ir paties miesto formavimui. Tekste išskiriamos ir aptariamos kai kurios aiškiau matomos aikščių formavimo tendencijos bei idėjos.Reikšminiai žodžiai: miesto morfologija, viešoji erdvė, aikštė, semiologinis tekstas, tendencijos.First Published Online: 22 May 2013